Lack of Usefulness of Donor-Derived Cell-Free DNA as a Biomarker for Cardiac Allograft Vasculopathy: A Prospective Study - Jiménez-Blanco Bravo, Marta; Pérez-Gómez, Laura; Hernández-Pérez, Francisco J.; Arellano-Serrano, Carlos; Torres-Sanabria, Mario; Gómez-Bueno, Manuel; Oteo-Domínguez, Juan F.; Mingo-Santos, Susana; Segovia-Cubero, Javier (Frontiers in Cardiovascular Medicine, 2022)
Background Cardiac allograft vasculopathy (CAV) remains a major cause of morbidity and mortality among long-term heart transplant recipients. There is an unmet need for a non-invasive biomarker of CAV that could obviate the need to perform surveillance coronary angiograms in these patients. Our aim was to evaluate the performance of Donor-derived Cell Free DNA (dd-cfDNA) as a biomarker of CAV. Methods We prospectively measured dd-cfDNA levels in all patients undergoing routine coronary angiography >1 year after heart transplant at a single center. Endpoints included the association between dd-cfDNA levels and the presence CAV, according to several prespecified criteria. Results We included 94 heart transplant recipients, a median of 10.9 years after transplant. Coronary angiogram revealed CAV0, CAV1, CAV2, and CAV3 in 61, 19, 14, and 6% of patients, respectively. Comparison of dd-cfDNA levels in patients with CAV0 and CAV1–2–3 (primary end-point) did not show significant differences (0.92%, IQR 0.46–2.0 vs. 0.46%, IQR 0.075–1.5, p = 0.059), nor did the comparison between patients with stable CAV (no new coronary lesions since previous angiogram, n = 77) and progressive CAV (n = 17); dd-cfDNA values 0.735% (IQR 0.195–2.0) vs. 0.9% (IQR 0.12–1.8), p = 0.76. However, we found an association between NTproBNP levels and CAV degree (p = 0.017). Dd-cfDNA levels did not correlate with NTproBNP (ρ = −0.095). Conclusion In this study, dd-cfDNA did not perform as a useful biomarker to avoid surveillance coronary angiograms for CAV diagnosis. Clinical Trial Notation Potential Role of Donor-derived Cell Free DNA as a Biomarker in Cardiac Allograft Vasculopathy, NCT 04791852.